Assessing the Functionality of PAI KKG Program in Improving Professional Competence: A CIPP Model Study in Kapanewon Cangkringan - Nurulita, Aprilia; Fatimah, Zulfida Aulia; Suwadi (Universitas Islam Indonesia, 2025)
Although intended to develop teacher’s competence and professionalism, the KKG forum is often conducted to address practical classroom issues. Thus, this research was conducted to evaluate the context, input, process and product components of the PAI KKG program in Kapanewoman Cangkringan. This study employed an evaluative qualitative approach using the CIPP model. Data collection techniques included interviews, observations and document studies. The results showed: (1) Context, the KKG PAI program in Kapanewon Cangkringan has not fully followed the technical guidelines procedures that have been made, especially in terms of developing teachers' professional competence. (2) Input, all components of the teachers' working group activities have met the needs but there are still obstacles in each component. (3) Process, the Kapanewon Cangkringan PAI teachers' working group program cannot all be implemented according to the scheduled activities. This is due to other factors from both the school and the teachers' personalities. (4) Product, although the Kapanewon Cangkringan teachers' working group program did not run as expected, it has achieved some improvements in student achievement each year. The study reveals that the KKG PAI program in Kapanewon Cangkringan has not function optimally, as various obstacles continue to hinder these activities, thus affecting the results of PAI teachers' professional competence.